DIGITAL ARREST SCAMS IN INDIA: CHALLENGES AND SOLUTIONS WITH SPECIAL REFERENCE TO KARNATAKA - Dr. R. N. Mangoli (IJRDO - Journal of Social Science and Humanities Research, 2025)
The digitization of India’s economy and public services has been paralleled by a surge in sophisticated cybercrimes. Among the most pernicious is "Digital Arrest," a hybrid psychological and financial fraud that leverages authority impersonation and digital isolation to extort victims. This study provides a comprehensive analysis of Digital Arrest scams in India, with a focused investigation into Karnataka State, a leading tech hub disproportionately targeted by such crimes. This research employs a mixed-methods approach, analyzing secondary data from the National Crime Records Bureau (NCRB), the Indian Cyber Crime Coordination Centre (I4C), and Karnataka Police reports from 2020 to 2024. A systematic review of news reports, victim testimonials, and advisories from the Ministry of Home Affairs was conducted to deconstruct the modus operandi. The study synthesizes this metadata to quantify economic losses, identify victim demographics, and map the operational infrastructure of these scams. The analysis reveals a dramatic increase in Digital Arrest cases, with reported losses exceeding ₹200 crore nationally in 2023-24. Karnataka, particularly Bengaluru, emerges as a major hotspot, accounting for nearly 20% of high-value cases. The modus operandi is highly organized, involving spoofed calls from fake law enforcement IDs, the use of deepfake technology for intimidation, and real-time psychological manipulation to keep victims in a state of coerced compliance. The primary challenges identified include jurisdictional complexities, the use of encrypted cross-border communication, insufficient cyber literacy among the general public, and the rapid evolution of social engineering tactics. Digital Arrest represents a critical threat to national security and individual financial safety. Combating it requires a multi-pronged solution framework. This paper proposes a consolidated strategy involving Technology (AI-driven detection of spoofed calls and fraudulent financial transactions), Legislation (fast-track courts and stricter KYC for digital payment platforms), Enforcement (dedicated cyber-psy-ops units within police forces), and Awareness (nationwide, vernacular digital hygiene campaigns). The implementation of this integrated "TELA Framework" is imperative to build resilience against this evolving form of cyber-terrorism.